Behavioral pricing - Estelani, Hooman; Maxwell, Sarah (Journal of Product & Brand Management., 2004)
Price management is one of the most central and sensitive elements of the process of managing a successful brand. Even a small change in price can have a disproportionate change in profitability, thereby increasing the importance of accurate and scientific ways of determining optimal prices. Previously published in: Journal of Product & Brand Management, Volume 13, Number 6, 2004.